Challenges, Advances and Opportunities in Exploring Natural Products to Control Arboviral Disease Vectors - Demarque, Daniel P.; Espindola, Laila S. (Frontiers in Chemistry, 2021)
Natural products constitute an important source of molecules for product development. However, despite numerous reports of compounds and active extracts from biodiversity, poor and developing countries continue to suffer with endemic diseases caused by arboviral vectors, including dengue, Zika, chikungunya and urban yellow fever. Vector control remains the most efficient disease prevention strategy. Wide and prolonged use of insecticides has resulted in vector resistance, making the search for new chemical prototypes imperative. Considering the potential of natural products chemistry for developing natural products-based products, including insecticides, this contribution discusses the general aspects and specific characteristics involved in the development of drug leads for vector control. Throughout this work, we highlight the obstacles that need to be overcome in order for natural products compounds to be considered promising prototypes. Moreover, we analyze the bottlenecks that should be addressed, together with potential strategies, to rationalize and improve the efficiency of the drug discovery process.